Perancangan Alat Pengatur Jarak Pengunjung Museum Menggunakan Sensor Ultrasonik Berbasis Mikrokontroler At89s51 - Eko Setia Budi; Raden Bagus Dimas Putera; Abdul Rahman Kadafi (STMIK Budi Darma, 2019)
In the current era of globalization, the rapid advance of information technology. The computer is the equipment created to facilitate human work, while achieving good progress in the manufacture of hardware or software. For that I am as a writer tries Final for the manufacture of a tool called